Formulasi Tepung Sagu Dan Tepung Kacang Merah Terhadap Pembuatan Kukis - Ramadan, Yusirwan; Augustyn, Gelora H; Mailoa, Meitycorfrida (Universitas Pattimura, 2023)
This is to find the best formulation for treating sago flour and red bean flour in making cookies that the panelists like. The design used was a completely randomized design (CRD) consisting of 6 treatments. The treatment used was the ratio between sago flour and red bean flour (100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, and 50%:50%). The observed data were proximate analysis and organoleptic. The results of the study with the sago flour formulation: red bean flour in the P3 treatment was the best treatment in making cookies with chemical test results, namely 4.73% water content, 1.57% ash content, 6.73% protein content, 8.70 fat content % and carbohydrate content of 78.25%. At the same time, the organoleptic test was slightly brownish yellow in color, savory taste, crunchy texture, and overall (overall) liked by the panelists. Meanwhile, according to SNI, the cookies produced are also according to standards except for protein and fat content.